ANALYSIS OF SEARCH ENGINE MARKETING EFFECTIVENESS FOR CUSTOMER PERCEPTION AND CUSTOMER LOYALTY AT PHITAGORAS TRAINING AND CONSULTING - Indra Kurniadi; M. Gunawan Alif (Journal of Business Strategy and Execution, 2014)
PT. Phitagoras Global Duta, established in 2003, is a training and consulting provider dedicated to support organizations, in all sectors of business, industry and government.  Phitagoras provide a wide range of consulting and training services in the area of Quality/Productivity, Environmental, Occupational Health and Safety and Laboratory. Began in 2007, Phitagoras started to enhance their market with Search Engine Marketing (SEM) implementation. This strategy has a significant impact into their company’s growth. The customer could easily find Phitagoras on the first page result on Search Engine. The inquiry from customers increased significantly, they are coming from various companies, from oil and gas, mining, manufacturing, services industry, and education. The purpose of this research is to explain the Search Engine Marketing effectiveness for customer perception and customer loyalty in Phitagoras training and consulting. This research test the correlation between Search Engine Marketing with Customer perception and customer loyalty using correlation analysis and check the effect of Search Engine Marketing for customer perception and customer loyalty using Structural Equation Modeling (SEM) analysis.This research found that the Search Engine Marketing has a positive correlation in moderate level with customer perception and customer loyalty. Search Engine Marketing does not directly affect the Customer Loyalty, but Search Engine Marketing influence indirectly to Customer Loyalty through Customer Perception, because Search Eengine Marketing has significant effect on Customer Percetion and Customer Perception has significant effect on Customer Loyalty. In other words, Customer Peception act as mediating variables that mediate the effects of Search Engine Marketing on Customer Loyalty.